Correlation Between Parents Level of Education and Dental and Oral Hygiene in Children with Autism at Mutiara Hati Special School - Lita Agustia; Aulia Dwi Maharani; Syamsulina Revianti; Kezia Sepdwiningtyas Santoso (Denta Journal Kedokteran Gigi, 2021)
Background: Children with autism have difficulty controlling the movement of tongue that food often cannot perfectly swallowed . Parents play a very important role in maintaining dental and oral hygiene for children with autism. The behavior of children with autism is strongly influenced by the parent’s level of education. Objective: to determine the correlation between parent’s level of education and the level of oral hygiene in children with autism (measured by OHI-S). Methods: This type of research is analytic observational, with a cross sectional approach. Simple random sampling technique was performed. The total sample was 23 students of Mutiara Hati Surabaya Autism Special School. OH Index form by WHO was used to collect the data of dental hygiene and a questionnaire form by RISKESDAS was used to collect data of parent’s level of education. Results: There is a significant correlation between the parent’s level of education and OHI-S in children with autism (<0.05) ,R = -0.49 means the correlation is sufficient. The lower the level of dental and oral hygiene the higher the level of education of their parents. Conclusion: There is a correlation between the parent’s level of education and dental and oral hygiene in children with autism at Mutiara Hati Special School.